Численный анализ стационарного перемешивания, вызванного системой точечных вихрей - Роговой, Н. С. (ХНУРЕ, 2013)
Проведено математическое моделирование процесса перемешивания вязкой несжимаемой жидкости в прямоугольной области. В области рассмотрен набор точечных вихрей. Найдено аналитическое выражение для функции тока с помощью метода R-функций. Изучено движение частиц жидкости при разных положениях вихрей. We model process of mixing of a viscous incompressible liquid in rectangular area. The set of point vortexes was put to this area. To find analytical expression for a stream function, a structural-variational method of R-functions was used. Movement of particles of a liquid was modelled with different positions of vortexes. We find and investigate periodic points: areas of intensive mixing.
Keywords: перемешивание; квазипериодические течения; вязкая несжимаемая жидкость; непротекаемая и неподвижная граница; краевая задача для функции тока; process of mixing; viscous incompressible liquid; stream function; method of R-functions